Pohjaveden pinnankorkeuden ja laadun muutokset Suomessa 1999-2012 - Leponiemi, Laura (Helsingfors universitet, 2014)
In groundwater sites located in Sodankylä, Lumiaho, Taikkomäki and Tullinkangas data has been collected from natural state springs for quality and from groundwater pipes for groundwater level studies. Quality measurements and groundwater level changes has been studied graphically and statistically to understand the variation and the cause and effect phenomena of hydrological processes. Quality parameters and groundwater level results has been compared to a time series study: ‘Groundwater level and quality changes in Finland 1975-1999’ by Finnish Environmental Institute and to the regulation 401/2001 about quality requirements for water in household consumption by Ministry of Social Affairs and Health. Groundwater level fluctuation has been compared with changes in precipitation and evaporation rates close to research sites, and with the typical behaviour of groundwater level in related regimes. Precipitation and evaporation data has been measured for each groundwater site from the closest meteorological stations. Evaporation has also been calculated using the Hamon equation. The quality measurements include the following parameters: pH, electrical conductivity, nitrite-nitrate as nitrogen, ammonium as nitrogen, oxygen, phosphate as phosphorus, iron and manganese. Despite the fact that chosen research sites represent natural state areas, human behaviour has had a noticeable effect on groundwater level and quality. In all measurement sites the pH results are in most cases more acidic and conductivity results smaller than they should be in water with good quality. However, these results have improved within last ten years in most cases. The values of nitrite-nitrate and ammonium were mostly good and median values were mostly outstandingly lower than the results measured before. The values of oxygen and phosphate were good. Also, with the exception of Sodankylä, the values of iron and manganese were good. Groundwater levels in research sites followed more or less the water levels related to each regime. In the very ...